2012
DOI: 10.1097/jom.0b013e31824329ab
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Workplace-Based Weight Loss Program on Work-Related Outcomes in Overweight Male Shift Workers

Abstract: The Workplace POWER weight loss program improved a number of important work-related outcomes in male shift workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
151
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(155 citation statements)
references
References 32 publications
0
151
0
4
Order By: Relevance
“…Sample size is another area for improvement. In this review, only three studies reported sample sizes with adequate power to detect a statistically significant difference in primary outcomes of interest (36,58,59,63).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sample size is another area for improvement. In this review, only three studies reported sample sizes with adequate power to detect a statistically significant difference in primary outcomes of interest (36,58,59,63).…”
Section: Discussionmentioning
confidence: 99%
“…However, improvements were not universal or consistent in magnitude across studies and studies with higher quality scores appeared to find less favorable changes. Again, because shift-scheduling changes were generally implemented across workplaces, randomiza- (56,57), body composition, blood pressure, and physical activity (58,59). This suggests that lifestyle habits may not improve spontaneously among shift workers as a result of shift schedule changes, and interventions specifically targeted at improving lifestyle behaviors may be necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This emphasizes the importance of introducing programs aimed at weight loss, with the objective of improving workers' health, productivity and self-esteem. Research conducted in Australia sought to conduct intervention through sessions of education, physical activity for overweight and obese men at an aluminum company, observing that in 14 weeks, there was an average loss of 4.4 kg (18) . Confirming previous research, in the interior of the state of São Paulo, Brazil, a program was established with the same aims of the research conducted in Australia, but with the introduction of healthy foods in the company's restaurant, so that workers would acquire healthy habits and apply them outside the work environment (38) .…”
Section: Physical Activities and Health Carementioning
confidence: 99%
“…Several studies have investigated the particular problems overweight people face at work: their personal protective equipment that may not fit their anthropometric characteristics, 1 the main professions that are associated with obe-a r t i c l e sity, especially men working in transport, 2 professional factors, especially the impact of shift work, which increases the risk of being overweight, [3][4][5] macroeconomic consequences, 6 and increased work injuries and absenteeism. 3,[6][7][8][9][10] Obese people often undergo discrimination at work. 7,[11][12][13] Programs of intervention to reduce weight have been also tested by companies with short-term but not long-term efficiency.…”
Section: Introductionmentioning
confidence: 99%